Women entrepreneurs in the OECD. Key evidence and policy challenges - Piacentini, Mario (Paris, 2013)
"Important gender gaps in entrepreneurship exist. Men are three times more likely than women to own a business with employees. Women rarely own large businesses and their average earnings from selfemployment are up to 60% lower than for men. Cultural norms, stereotypes and lack of role models make women less interested in an entrepreneurial career and less confident in their capacities as entrepreneurs. Other obstacles such as time shortages and the composition of their professional networks lead women to start relatively small businesses, with low levels of initial capital and bank financing. These obstacles establish a competitive disadvantage for companies owned by women, which translates in levels of labour productivity that are 5 to 30% lower than those of companies owned by men. This paper also presents examples of policy initiatives in the domains of credit, training and awareness raising that can unlock the double dividend of women’s entrepreneurship: higher empowerment of women and more productive businesses. Better data and more analysis are an essential precondition for a more effective implementation of these policies."